Penguatan Rantai Pasok Rajungan Berbasis Keadilan Gender dan Ekonomi Biru di Dusun Puyahan, Desa Lembar Selatan, Lombok Barat - Marzuki, Muhammad; Abidin, Zaenal; Setyono, Bagus Dwi Hari; Affandi, Rangga Idris; Diamahesa, Wastu Ayu; Angga, Prayogi Dwina; Rahmadani, Thoy Batun Citra; Sumsanto, Muhammad; Diniariwisan, Damai; Alim, Sahrul (Jurnal Gema Ngabdi, 2025)
Puyahan Hamlet in South Lembar Village is one of the traditional crab peeling centers (Portunus pelagicus) on the west coast of Lombok Island. Women in the informal work system dominate this activity without social protection or quality standards. Despite playing an important role in Indonesia's crab export supply chain, women peelers still face major challenges in technical and institutional aspects. This service activity aims to increase technical capacity and strengthen the institution of women crab peeler groups through training in the processing of fishery products based on the principles of food sanitation and facilitating the formation of legal business organizations. The methods used include participatory social mapping, technical training based on Good Manufacturing Practices (GMP) and Sanitation Standard Operating Procedures (SSOP), group institutional formation, and participatory evaluation. The results of the training showed a significant improvement in participants' hygiene understanding and practices, with an average pre-test score of 35.4 and a post-test score of 82.1. In addition, the establishment of organizational structures and institutional legalization allowed groups access to advanced training and wider economic opportunities. This intervention has been proven to be able to encourage behavior change, strengthen women's socio-economic position in the fisheries value chain, and support the gender empowerment agenda in coastal areas in a sustainable manner. The program recommends replication in other coastal areas with a gender-responsive participatory approach to strengthen the economic resilience of women's fishing communities.